Effect of ripening with Penicillium roqueforti on texture, microstructure, water distribution and volatiles of chicken breast meat. (13th December 2018) - Guo, Liping; Yu, Bing; Wang, Shuling; Zhu, Yinglian; Li, Peng; Wang, Baowei; Huang, Ming; Sun, Jingxin
Summary: In this study, the influence of ripening with Penicillium roqueforti on texture, microstructure, protein structure, water mobility and volatile flavour compounds of chicken breast meat was investigated. Scanning electron microscopy (SEM) and transmission electron microscope (TEM) images showed that the granule formed and chicken myofibril fractured after ripening. Reduction in α‐helix and increases in β‐sheet structure content accompanied by decrease in hardness and springiness and increase in gumminess were found in ripened chicken breast meat. Low field nuclear magnetic resonance (LF‐NMR) revealed that increasing intra‐myofibrillar water and decreasing extra‐myofibrillar water resulted in the higher water‐holding capacity after ripening with P. roqueforti . In addition, chicken breast meat ripened with P. roqueforti contained more volatile flavour compounds, in particular aldehydes. Abstract : High‐pressure steam sterilized chicken breast meat was firstly inoculated with Penicillium roqueforti at 27 ± 1 °C for 7days, then immersed in 4% sodium chloride solution and ripened at 30 ± 1 °C and 60±5% relative humidity for 14 days. Finally, palatable chicken breast products with better texture, improved microstructure and higher water‐holding capacity were successfully obtained.